The effects of eccentric exercise-induced fatigue on position sense during goal-directed movement - Grose, G.; Manzone, D. M.; Eschelmuller, G.; Peters, R. M.; Carpenter, M. G.; Inglis, J. T.; Chua, R. (Journal of Applied Physiology, 2022)
We investigated the impairment of position sense associated with muscle fatigue. In Experiment 1, participants performed learned eccentric extension (22°/s) movements of the elbow as the arm was pulled through the horizontal plane without vision of the arm. They opened their closed right hand when they judged it to be passing through a target. Dynamic position sense was assessed via accuracy of limb position to the target at the time of hand opening. Eccentric movements were performed against a flexion load [10% of flexion maximum voluntary contractions (MVCs)]. We investigated performance under conditions with and without biceps vibration, as well as before and after eccentric exercise. In Experiment 2, a motor was used to extend the participant`s limb passively. We compared conditions with and without vibration of the lengthening but passive biceps, before and after exercise. In Experiment 1, vibration of the active biceps resulted in participants opening their hands earlier [mean, x(95% confidence interval, CI) -5.52° (-7.40, -3.63)] compared with without vibration. Exercise reduced flexion MVCs by ~44%, and participants undershot the target more [-5.51° (-9.31, -1.70)] in the post-exercise block during control trials. Exercise did not influence the persistence of the vibratory illusion. In Experiment 2, vibration resulted in greater undershooting [-2.99° (-3.99, -1.98)] compared with without vibration, before and after exercise. Although exercise reduced MVCs by ~50%, the passive task showed no effects of exercise. We suggest that the central nervous system continues to rely on muscle spindles for limb position sense, even when they reside in a muscle exposed to fatiguing eccentric contractions.